Level of Interleukins IL-6 and IL-15 in Blood Plasma of Mice after Forced Swimming Test - Kapilevich L. V. Leonid Vladimirovich; Kironenko T. A. Tatjyana Aleksandrovna; Zakharova A. N. Anastasiya Nikolaevna; Kabachkova A. V. Anastasiya Vladimirovna; Orlov S. N. Sergey Nikolaevich (2016, 2016)
Title screen